Non-Invasive Brain Stimulation in Children With Unilateral Cerebral Palsy: A Protocol and Risk Mitigation Guide - Gillick, Bernadette T.; Gordon, Andrew M.; Feyma, Tim; Krach, Linda E.; Carmel, Jason; Rich, Tonya L.; Bleyenheuft, Yannick; Friel, Kathleen (Frontiers in Pediatrics, 2018)
Non-invasive brain stimulation has been increasingly investigated, mainly in adults, with the aims of influencing motor recovery after stroke. However, a consensus on safety and optimal study design has not been established in pediatrics. The low incidence of reported major adverse events in adults with and without clinical conditions has expedited the exploration of NIBS in children with paralleled purposes to influence motor skill development after neurological injury. Considering developmental variability in children, with or without a neurologic diagnosis, adult dosing and protocols may not be appropriate. The purpose of this paper is to present recommendations and tools for the prevention and mitigation of adverse events during NIBS in children with unilateral cerebral palsy (UCP). Our recommendations provide a framework for pediatric NIBS study design. The key components of this report on NIBS adverse events are a) a summary of related literature to provide the background evidence and b) tools for anticipating and managing adverse events from four international pediatric laboratories. These recommendations provide a preliminary guide for the assessment of safety and risk mitigation of NIBS in children with UCP. Consistent reporting of safety, feasibility, and tolerability will refine NIBS practice guidelines contributing to future clinical translations of NIBS.